Academic amidst Pandemic: A Survey of the Learning Experiences among Filipino Undergraduate Students - Arvy James C. de Guzman (Researchparks Publishing, 2022)
The global spread of Covid-19 has brought significant changes in the lives of many people around the globe and has forced many educational institutions to move from the traditional in person classes to online mode of learning. Thus, there is a need to know the learning experience of the student’s despite of the sudden shift in the mode of learning. In lieu of this matter, the objective of this study is to understand the undergraduate student’s learning experiences 2 years after the global outbreak of COVID-19. This study employed an adapted Questionnaire from the study of Zhou & Zhang (2021) and surveyed 60 undergraduate students. The result of the study implies that there is a positive overall learning experience among the undergraduate students but they have a low level of mental health. The study also discovers that the undergraduate Students have an average perception of the learning community during the pandemic and they received a sufficient amount of student and peer support. Moreover, it has been found out through this study that there are more hindrances than benefits in this kind of learning set up.